Association between idiopathic pulmonary fibrosis and coronary artery disease: a case-control study and cohort analysis - Kim, Won-Young; Mok, Yejin; Kim, Go Woon; Baek, Soo-Jin; Yun, Young Duk; Jee, Sun Ha; Kim, Dong Soon (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2015)
Background: Although the increased risk of coronary artery disease (CAD) in the patients with idiopathic pulmonary fibrosis (IPF) has been reported, there was few detailed information on the risk factors for CAD in IPF. The aim of this study was to investigate the prevalence of CAD in IPF with analysis of other risk factors. Methods: The subjects were 460 patients (mean age, 65 years; 79% male; 74% current or ex-smoker) diagnosed as IPF at Asan Medical Center and 1,925 controls matched with age, gender, smoking habits, and date of IPF diagnosis from the cohort of Korean Heart Study. Cardiovascular risk factors and prevalence of CAD in both groups were compared and the incidence of newly developed CAD during follow-up was also analyzed. Results: IPF group was more diabetic, and control group had a higher proportion of hypertension and hypercholesterolemia. The prevalence of CAD in IPF group (7%) was two times higher than that of control group (3%). Multivariate analysis revealed that age (OR, 1.04; 95% CI, 1.02-1.07), hypertension (OR, 2.13; 95% CI, 1.36-3.33), hypercholesterolemia (OR, 3.85; 95% CI, 2.51-5.88), and IPF (OR, 2.64; 95% CI, 1.68-4.14) were significant risk factors for CAD. During follow-up (median: 2.5 years for IPF and 4.4 years for controls), the incidence of newly diagnosed CAD was higher in the patients with IPF (6.8%) compared to controls (2.8%) (RR, 1.92; 95% CI, 1.08-3.43). Conclusions: IPF itself was an independent risk factor for CAD after the adjustment of age, hypertension, diabetes, and hypercholesterolemia.